Antibacterial activity of Trigona sp. propolis extract against Aggregatibacter actinomycetemcomitans in vitro - Yuni Yuni; Sumitro Sumitro; Angelin Nehemia Juniarti Butarbutar; Linda Novelgia Setiawan; Shirley Adriana; Bella Fernanda (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Aggregatibacter actinomycetemcomitans is a primary pathogen in aggressive periodontitis. Plaque control uses chemical and natural agents. Propolis inhibits growth of bacteria, viruses, and fungi. This study assessed the in vitro antibacterial activity of Trigona sp. propolis extract against A. actinomycetemcomitans. Methods: This true experimental laboratory study used a post-test-only control group design. Samples were A. actinomycetemcomitans bacteria in 8 groups (n=5 each). The dilution method tested antibacterial activity. Data analysis used Kruskal-Wallis and Mann-Whitney tests.  Results: Mean A. actinomycetemcomitans colony counts (mean ± SD) were 5.60 ± 1.52, 11.60 ± 4.83, 15.60 ± 5.03, 22.20 ± 2.86, 25.40 ± 6.43, and 141.80 ± 5.40 for propolis concentrations of 50, 25, 12.5, 6.25, 3.125, and 1.56, respectively. Negative control (DMSO) showed uncountable colonies; positive control (chlorhexidine) showed none. Kruskal-Wallis test indicated significant differences (p=0.001). Mann-Whitney test showed differences between most groups (p<0.05), except 25 vs. 12.5% (p=0.421), 12.5 vs. 3.125% (p=0.056), and 6.25 vs. 3.125% (p=0.151).  Conclusion: Trigona sp. propolis inhibited and showed bactericidal potential against A. actinomycetemcomitans in vitro, with minimum inhibitory concentration at 3.125% and minimum bactericidal concentration at 50%.